2011
DOI: 10.1002/app.33521
|View full text |Cite
|
Sign up to set email alerts
|

Alcohophilic gels: Polymeric organogels composing carboxylic and sulfonic acid groups

Abstract: The clinical significance of an interstitial duplication of chromosome 15q11q13 is still not well documented. This abnormality has been associated with autistic spectrum disorders (ASD) and varying degrees of mental retardation. The clinical variability appears to be influenced by the parental origin of the duplication. We present here the clinical evaluation and psychological assessment of the largest reported family with 12 carriers on three generations. Patients exhibit mental retardation, motor and visuo‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…4,5 Kabiri et al prepared super alcogels based on three constituents namely 2-Acrylamido-2-methylpropane sulfonic acid, poly(ethylene glycol) macromer, and acrylic acid (AAc). 6,7 The alcohol absorbency of poly(AAc) was reported by Zhao and Liu. 8 The gel was synthesized by using γ ray as the initiator and Zn 2+ or Ni 2+ as a cross-linker.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…4,5 Kabiri et al prepared super alcogels based on three constituents namely 2-Acrylamido-2-methylpropane sulfonic acid, poly(ethylene glycol) macromer, and acrylic acid (AAc). 6,7 The alcohol absorbency of poly(AAc) was reported by Zhao and Liu. 8 The gel was synthesized by using γ ray as the initiator and Zn 2+ or Ni 2+ as a cross-linker.…”
Section: Introductionmentioning
confidence: 89%
“…9 Copolymers of AAc with AMPS were prepared through solution polymerization and their alcohol absorbency was investigated in different low molecular weight alcohols. 6 Organogels can be used in separation of solvents, controlled release of fragrance 8,10,11 and for super absorbency of alcohols, such as methanol and ethanol, which are used as fuel gels, fire starters, hand sanitizers etc. 6,12 In the present work, an attempt has been made to synthesize polymer organogels based on NTBA (N-tertiary butyl acrylamide, which is synthesized and characterized at our laboratory) and AAc.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that probability of counterion binding in sulfonated monomer leads to decrease in alcohol absorbency. Thus, Na + cations in poly(AA-SAS) and poly(AA-SSS) were removed by acid treatment to increase alcohol absorbency [5,6]. Such acid-treated poly (AA-SSS) could absorb as high as 50 g/g ethanol and 80 g/g methanol [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, crosslinked poly(acrylic acid)(AA) by metal cation shown to absorb ethanol up to 158 g/g [3]. Copolymers based on sulfonated monomers such as 2-acrylamido 2-methl-propane sulfonic acid (AMPS) [4], sodium allyl sulfonate (SAS) [5], and sodium styrene sulfonate (SSS) [6] were also synthesized as alcogel. Alcohol is absorbed into such structures due to dissociation of ionic groups of sulfonated monomers [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation